Possibilities and Scope of Environmental Protection Through Criminal Law - the New Environmental Crime Directive: - Stojanović, Zoran; Bodrožić, Ivana (NBP. Nauka, bezbednosti, policija, 2025)
In a wider context of achieving European Green Deal objectives, seen through the prism of a new Environmental Crime Directive at the European Union level, the main purpose of this article is to examine, underline and prepare future changes within the national criminal law framework in terms of criminal law protection of the environment, so that it should be as efficient as possible, but at the same time constitute a rational system of criminal law provisions. The paper is divided in two main chapters.The first chapter deals with issues of criminal law protection of the environment, in general, the legitimacy of the environment as a separate protected value, the level of its social harmfulness and some nomotechnical characteristics of the relevant elements of the offences which need to fulfill common standards of their normative shaping. The second is dedicated to the structure, aims and goals of the new Environmental Crime Directive in fighting environmental crime, as a part of fulfilling processes of the European Green Deal. Changes in the area that defines new environmental crimes at the European Union level, minimum common standards in prescribing criminal sanctions, and enhancing the existing ones, as well as setting brand new tools and mechanisms in strengthening and enhancing the effectiveness of the law enforcement cooperation in the field of environmental crimes have been brought about by the new Environmental Crime Directive aimed to crack down on environmental crime, and they can be seen and marked as an important contribution to criminal law protection of the environment, but only seen as the ultimate instrument of the state reaction to environmental crimes. Even though environmental crimes have their negative impact on human health, safety and economics in general, they have to be realistically conceived and seen only as an ultima ratio societatis in protection of the environment.